Relevance of Neonatal Behavior Assessment Scale for Infants With Somatic Disorders: Comparison on One Matched Group of Control - Belot, Rose-Angélique; Bouteloup, Margaux; Mariage, André; Candilis-huisman, Drina; Mottet, Nicolas; Mellier, Denis (Frontiers in Pediatrics, 2021)
Objective: To compare NBAS (Neonatal Behavior Assessment Scale) results in two groups of infants with or without somatic disorder (N = 26). Method : The NBAS was administered to 2 groups (clinical and control) of 13 infants each aged from to 5 to 18 weeks, matched 2 by 2 according to sex, age, rank among siblings and parental socio-professional category. The first group includes infants with somatic disorder (clinical) and is matched with a second group of “healthy infants” (control). Results: Results indicate that the mean score of control group is significantly higher than that of the clinical group. Most of items are affected by the presence of a somatic disorder. Indeed, 5 out of the 6 categories present a statistically significant difference in favor of the control group, more specifically for the items “state regulation”, “motor system” and “orientation/interaction”. Conclusion: This exploratory research enables a precise description of infants’ difficulty in regulating excitations and of the impact of somatic disorders on their development. These innovative knowledge will assist pediatricians and health professionals in the understanding of infants’ characteristics to develop an adapted-care.